HUBUNGAN KEDISIPLINAN SISWA DAN PRESTASI BELAJAR KELAS III DI SDN SUKASARI 4 KOTA TANGERANG - Noviana Safitri; Kanzha Mecca Rajabi; Anggun Melani Putri; Rahmawati Eka Saputri (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the relationship between student discipline and academic achievement in elementary school. A descriptive qualitative approach was employed, with data collected through direct observation of third-grade students and semi-structured interviews with the third-grade homeroom teacher, Ms. Desti, at SDN Sukasari 4, Tangerang City. The findings revealed that among the 29 observed students, 8 students (±28%) demonstrated high levels of discipline, 15 students (±52%) were categorized as having moderate discipline, and 6 students (±20%) showed low discipline. In terms of academic achievement based on semester report cards, 10 students (±35%) achieved high academic performance, 13 students (±45%) were in the moderate category, and 6 students (±20%) had low performance. The results indicate that students with higher levels of discipline tend to achieve better academic outcomes, as reflected in scores above the minimum competency standard and consistent task completion. Conversely, students with lower discipline levels often face learning difficulties. This study underscores the importance of instilling disciplined behavior, cultivated by teachers at school and supported by parents at home, in enhancing students' academic success.